Genetics of Endometrial Cancers - Tsuyoshi Okuda; Akihiko Sekizawa; Yuditiya Purwosunu; Masaaki Nagatsuka; Miki Morioka; Masaki Hayashi; Takashi Okai (Obstetrics and Gynecology International)
Endometrial cancers exhibit a different mechanism of tumorigenesis and progression depending on histopathological and clinical types. The most frequently altered gene in estrogen-dependent endometrioid endometrial carcinoma tumors is PTEN. Microsatellite instability is another important genetic event in this type of tumor. In contrast, p53 mutations or Her2/neu overexpression are more frequent in non-endometrioid tumors. On the other hand, it is possible that the clear cell type may arise from a unique pathway which appears similar to the ovarian clear cell carcinoma. K-ras mutations are detected in approximately 15%–30% of endometrioid carcinomas, are unrelated to the existence of endometrial hyperplasia. A β-catenin mutation was detected in about 20% of endometrioid carcinomas, but is rare in serous carcinoma. Telomere shortening is another important type of genomic instability observed in endometrial cancer. Only non-endometrioid endometrial carcinoma tumors were significantly associated with critical telomere shortening in the adjacent morphologically normal epithelium. Lynch syndrome, which is an autosomal dominantly inherited disorder of cancer susceptibility and is characterized by a MSH2/MSH6 protein complex deficiency, is associated with the development of non-endometrioid carcinomas.